2023
DOI: 10.1002/cbic.202200694
|View full text |Cite
|
Sign up to set email alerts
|

Hofmeister Series: From Aqueous Solution of Biomolecules to Single Cells and Nanovesicles

Abstract: Hofmeister effects play a critical role in numerous physicochemical and biological phenomena, including the solubility and/or accumulation of proteins, the activities of enzymes, ion transport in biochannels, the structure of lipid bilayers, and the dynamics of vesicle opening and exocytosis. This minireview focuses on how ionic specificity affects the physicochemical properties of biomolecules to regulate cellular exocytosis, vesicular content, and nanovesicle opening. We summarize recent progress in further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Figure 5 shows both raw data (Figure 5D,F) and the areas encircled by the hysteresis curves (Figure 5E,G). Historically, the Hofmeister effect has been associated with protein stability and denaturation phenomena [50][51][52]. While the effect has been demonstrated in the context of channel-facilitated transport, to the best of our knowledge, it has not previously been linked to changes in channel We observed that the rate of the voltage-induced transition to the closed state is contingent on the ion species and follows the Hofmeister series [50,51] (Figure 5).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Figure 5 shows both raw data (Figure 5D,F) and the areas encircled by the hysteresis curves (Figure 5E,G). Historically, the Hofmeister effect has been associated with protein stability and denaturation phenomena [50][51][52]. While the effect has been demonstrated in the context of channel-facilitated transport, to the best of our knowledge, it has not previously been linked to changes in channel We observed that the rate of the voltage-induced transition to the closed state is contingent on the ion species and follows the Hofmeister series [50,51] (Figure 5).…”
Section: Resultsmentioning
confidence: 76%
“…We observed that the rate of the voltage-induced transition to the closed state is contingent on the ion species and follows the Hofmeister series [50,51] (Figure 5). In our experimental approach, we applied a 150 mV potential to a single OmpF channel and measured the time spent in its fully open conformation [19].…”
Section: Resultsmentioning
confidence: 94%
“…The ability to reduce the degree of swelling and solubility of ST was Br − > Cl − > NO 3 − > SO 4 2− for anions and this order was consistent with the Hofmeister series. 9,10 In contrast to the structure-breaking ions, the structure-making ion; cosmotropic SO 4 2− anion led to a gradual decrease in the swelling at most with increasing Na 2 SO 4 salt concentration. The water losses increased with increasing anion valence, as larger anions promoted shrinkage.…”
Section: Resultsmentioning
confidence: 99%
“…Salt-induced swelling results of biocomposites with various starch content in sodium salts: NaBr, NaCl, NaNO 3 and Na 2 SO 4 showed that the anions reduced the swelling degree of semi-IPN biocomposites in the order of Br − > Cl − > NO 3 − > SO 4 2− , consistent with the Hofmeister series. 9,10 The effect of contact time and dye concentration on the adsorption process efficiency was investigated. The Langmuir, Freundlich, Dubinin–Radushkevich (D–R) and Temkin isotherm models were used to describe the equilibrium behavior of the adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident from this discussion that while some information on the influence of anions on the structural integrity of DNA in aqueous solutions is available, the implications of the chemical structure of anions of ILs are rather poorly understood. It is important to mention that the Hofmeister series encompasses a diverse range of anions characterized by variations in charge, shape, size, and hydrophobicity. These specific attributes of the anions can impact the interactions between ILs and DNA molecules. , For instance, hydrophobic anions exhibit an inclination to interact with the hydrophobic regions of DNA bases, thereby establishing significant associations. Conversely, the hydrophilic anions can facilitate the electrostatic interactions that take place between ILs and DNA.…”
Section: Introductionmentioning
confidence: 99%